(untitled) (Revista de Ciências Agroveterinárias, 2025)
The increasing use of soybean cultivars (Glycine max) with Xtend® technology facilitates the management of weeds that are resistant to some herbicides, through the use of auxin-mimicking herbicides in post-emergence soybean. However, the use of these herbicides on the crop is still uncertain for farmers due to the consequences on the plants. The objective of the study was to evaluate the effects of the Dicamba molecule on the morphological and productive characteristics of Xtend® soybean. The experiment was carried out in Augusto Pestana - RS, in the 2022/2023 harvest. Eight treatments were carried out, including pre- and post-emergence Dicamba application times for soybean cultivars with Xtend® technology. After each treatment, evaluations of the herbicide’s phytotoxicity symptoms and plant development were carried out on days 0, 3, 5, 7, and 15 after application. At harvest, all soybean productivity components of each plot were evaluated. Dicamba applications in the vegetative stage of soybean reduced the leaf area of the plants, but with immediate recovery. Applications of the herbicide in the reproductive stages of soybean compromised the number of viable flowers in the plants, being an irreversible damage.